The Effect of USA Monetary Policy on Energy Stock Markets: Evidence from European Union - Bernaoui, Mohamed Amine (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This thesis aims to forecast the effects of changes in the United States’ monetary policy on energy stock prices in Europe. Based on data availability, quarterly figures are constructed for energy related firms operating in the European countries. Using alternative econometric methods and various monetary policy tools, results generally confirm the long-term effects of the Federal Reserve’s monetary policy changes on energy stock variations in Europe. Policy implications and detailed discussions are provided results and conclusion sections of the thesis.

ÖZ: Bu tez, Amerika Birleşik Devletleri para politikasındaki değişikliklerin Avrupa'daki enerji hisse senedi fiyatları üzerindeki etkilerini tahmin etmeyi amaçlamaktadır. Veri mevcudiyetine dayalı olarak, Avrupa ülkelerinde faaliyet gösteren enerji ile ilgili firmalar için üç aylık rakamlar oluşturulmuştur. Alternatif ekonometrik yöntemler ve çeşitli para politikası araçlarını kullanan sonuçlar, genel olarak Federal Rezerv'in para politikası değişikliklerinin Avrupa'daki enerji stoku değişimleri üzerindeki uzun vadeli etkilerini doğrulamaktadır. Politika çıkarımları ve ayrıntılı tartışmalar, tezin sonuç ve sonuç bölümlerinde verilmektedir.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2022. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance Department; Energy Stock Markets--USA Monetary Policy; Energy--Economics; Stock Price; Energy; Monetary Policy; Cointegration; GMM